FLSP STUDENTS’ ANXIETY AND THEIR LEARNING STRATEGIES IN SPEAKING CLASS - Roro Millatu Al Ghaniy (University of Muhammadiyah Malang, 2023)
This study investigated the Foreign Language for Specific Purposes (FLSP) students' anxiety and learning strategies in speaking instruction. To gain insight into FLSP students' speaking anxiety and learning strategies, this study applied a descriptive qualitative research design. A Foreign Language Classroom Anxiety Scale (FLCAS) questionnaire and a semi-structured interview were used to collect data from 26 FLSP students for the study. The results were described in percentages and elaborated in the description. The results regarding the students' anxiety revealed that 7 out of 26 students (27%) experienced low anxiety, 17 out of 26 students (65%) encountered moderate anxiety, and 2 (8%) students experienced high anxiety. Furthermore, the results regarding the students' learning strategies showed that strategies such as preparation, practicing before speaking, and positive thinking helped students reduce anxiety in FLSP speaking performance. Implementing the appropriate strategies in FLSP speaking is significant as learning FLSP is more complex than general or academic English as it involves numerous foreign terms.